Polyazole nanotube / multi-walled carbon nanotube / silk nanofiber flexible composite film, preparation method thereof and application thereof in flexible supercapacitor
Patent Information
- Application Number
- CN202611367526.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-04
- Publication Date
- 2026-10-27
AI Technical Summary
该技术实现了三种材料的复合,但这种基于先成膜后电沉积的制备方法在实际应用和生产中存在明显不足:(1)电沉积法生成的聚吡咯纳米线主要附着在预先成型的SNF/MWCNT基底膜的表面
[0029](1)相比于现有电化学沉积法存在生成的活性物质易堵塞基底孔隙,长期循环下性能衰减的问题。本发明采用先合成、后共混抽滤,将三种材料交织成多孔网络,聚吡咯采用了中空纳米管结构,能够有效缓冲充放电过程中的体积应变。使电解液能够在长期循环中不断向薄膜深层渗透,实现材料的深层活化。测试表明,本发明复合膜在5000次充放电循环后,电容保持率不降反升,解决了传统导电聚合物电极循环寿命差的问题。
Smart Images

Figure CN122978490A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of functional composite materials technology, and relates to composite electrode materials, particularly to a method for preparing a polypyrrole nanotube / multi-walled carbon nanotube / silk nanofiber composite film and its application in flexible supercapacitors. Background Technology
[0002] Against the backdrop of rapid development in flexible electronics and intelligent manufacturing technologies, electronic products, represented by smart wearable devices and flexible sensors, are gradually becoming mass-produced and practical. These products place higher demands on energy storage technologies, requiring power supply equipment to not only possess good electrochemical performance but also maintain a stable energy supply under bending, folding, and repeated deformation.
[0003] Lithium-ion batteries boast high energy density, but suffer from drawbacks such as high structural rigidity, significant safety risks, and limited cycle life. These shortcomings are particularly pronounced in flexible wearable applications, severely restricting their use. In contrast, flexible supercapacitors, with their rapid charging and discharging capabilities, ultra-high power density, ultra-long cycle life, and excellent safety, have become the preferred power source for wearable electronic products, attracting sustained attention from both academia and industry in recent years.
[0004] Electrode materials are the core components determining the performance of supercapacitors. Existing flexible electrode materials typically employ thin-film structures, designed by introducing electrochemically active substances onto or within a flexible substrate to achieve wearable electrochemical energy storage. Common flexible substrates include carbon cloth, graphene paper, carbon nanotube paper, fabrics, and plastics. Although some progress has been made in this area, the resulting products generally suffer from problems in practical applications, such as difficulty in balancing flexibility and conductivity, insufficient structural stability, easy shedding of active substances, and significant degradation of electrochemical performance after repeated mechanical deformation.
[0005] Silk nanofibers (SNFs) are a high-potential protein nanomaterial, possessing excellent biocompatibility, superior mechanical properties, high specific surface area, good film-forming ability, and stable properties. Polypyrrole nanotubes (PPyn) are a novel class of one-dimensional heterocyclic conjugated conductive polymers with high theoretical specific capacitance, good redox reversibility, and excellent stability. Multi-walled carbon nanotubes (MWCNTs) are carbon materials with radial dimensions on the nanometer scale and axial dimensions on the micrometer scale, often used to improve the conductivity and charge transport efficiency of supercapacitor electrode materials. Combining these three one-dimensional nanomaterials and adjusting their proportions can fully leverage their unique structural and property advantages, achieving functional complementarity and performance enhancement, thereby preparing flexible composite membrane electrodes with excellent flexibility, high conductivity, high specific capacitance, and long cycle life.
[0006] In their previous work, the inventors attempted to combine three materials—polypyrrole nanowires (the preparation method and morphology of which are different from the polypyrrole nanotubes involved in this invention), MWCNTs, and SNFs—into flexible electrode materials (Journal of EnergyStorage 141 (2026) 119562), providing a method for preparing a Pn-y@S / Mx electrode. This technique employs a stepwise molding method, first using a eutectic solvent to peel silk to obtain SNFs, then combining them with MWCNTs to prepare a conductive film through vacuum filtration, and finally placing the film in an electrolyte to grow polypyrrole nanowires in situ on the surface through electrochemical deposition. This technique achieves the composite of the three materials, but this preparation method based on film formation followed by electrodeposition has significant shortcomings in practical applications and production: (1) The polypyrrole nanowires generated by the electrodeposition method are mainly attached to the surface of the pre-formed SNF / MWCNT substrate film. This coating structure results in limited bonding force between polypyrrole and the skeleton; when faced with repeated bending, the rigid polypyrrole layer on the surface is prone to cracking or falling off, resulting in limited mechanical flexibility and capacitance retention of the device. After 250 bends at 90°, the capacitance retention drops to 94.9%. (2) During the electrodeposition process, the continuous uneven growth of polypyrrole will block the pores of the substrate surface, hindering the electrolyte from penetrating into the deep layer of the film, making it impossible to fully utilize the internal conductive network and active sites. In long-term charge-discharge cycles, the material will experience performance degradation, making it difficult to achieve deep activation of the material during long-term cycles. (3) The electrochemical deposition process has strict requirements on reaction conditions such as deposition environment, electrolyte composition, and current density, and the process control threshold is high. The single batch preparation cycle is long and the labor and energy costs are high. At the same time, this method is difficult to complete the preparation of large-size uniform films and is difficult to adapt to the needs of large-area, continuous large-scale industrial mass production.
[0007] In view of the shortcomings of the prior art, the technical problem to be solved by the present invention is: how to solve the problems of uneven distribution of active components, easy shedding of active materials and difficulty in large-scale production caused by electrodeposition method, and to provide a simplified process that meets the requirements of industrial mass production, while also achieving better cycle stability and mechanical flexibility. Summary of the Invention
[0008] To address the shortcomings of the existing technology, the present invention aims to provide a method for preparing a polypyrrole nanotube / multi-walled carbon nanotube / silk nanofiber composite membrane and its application in flexible supercapacitors.
[0009] The technical solution of the present invention is as follows:
[0010] A method for preparing a polypyrrole nanotube / multi-walled carbon nanotube / silk nanofiber composite membrane includes the following steps:
[0011] A. Preparation of silk nanofiber (SNF) dispersion:
[0012] Choline chloride and malonic acid were mixed in a molar ratio of 1:1 to 1:1.5 and stirred at 70-90 °C for 1-3 h to obtain a eutectic solvent. Degummed silk was added to this solvent; the mass ratio of degummed silk to eutectic solvent was 1:100 to 1:150, and the mixture was stirred in an oil bath at 100 °C for 36-48 h. The reaction was terminated by adding ethanol, and the resulting solution was obtained by centrifugation and washing. The SNF was dispersed in deionized water to obtain a dispersion with a mass concentration of 1-5 mg / mL.
[0013] B. Preparation of polypyrrole nanotubes (PPyn):
[0014] Methyl orange was dissolved in deionized water to form a solution. Ferric chloride (FeCl3·6H2O) was slowly added under continuous stirring until the reaction was complete, forming a reddish-brown flocculent precipitate. Pyrrole monomer was then slowly added dropwise, and the reaction was carried out for 12–36 h under ice-water bath and light-protected conditions. The resulting black PPyn was washed several times and dried in a vacuum drying oven at 60 °C for 24 h.
[0015] The molar ratio of methyl orange to ferric chloride is 1:8 to 1:12; the molar ratio of pyrrole monomer to ferric chloride is 1:0.8 to 1:1.2.
[0016] C. The mass ratio of PPyn, MWCNT, and SNF was 1~2:1~2:1. PPyn and MWCNT were added to the SNF dispersion (based on the mass of SNF in the dispersion). MWCNT was purchased from Chengdu Organic Chemical Co., Ltd., with specifications of purity ≥ 97wt%, length < 50 μm, and outer diameter 5-15 nm. The mixture was ultrasonically treated for 0.5~1.5 h, followed by stirring for 0.5~1.5 h to ensure uniform mixing of the three one-dimensional nanomaterials. The mixture was then vacuum filtered to form a membrane, which was subsequently freeze-dried to obtain a polypyrrole nanotube / multi-walled carbon nanotube / silk nanofiber composite membrane (abbreviated as PPyn / MWCNT / SNF; freeze-drying temperature and time were -60 °C and 24 h, respectively).
[0017] In a preferred embodiment of the present invention, in step A, the molar ratio of choline chloride and malonic acid in the eutectic solvent is 1:1.
[0018] In a preferred embodiment of the present invention, in step A, the preparation conditions of the eutectic solvent are: continuous stirring at 80 °C for 2 h.
[0019] In a preferred embodiment of the present invention, in step A, the preparation conditions of the SNF are: degummed silk is stirred at 100°C for 40 h in a eutectic solvent.
[0020] In a preferred embodiment of the present invention, in step B, the molar ratio of methyl orange and FeCl3 6H2O to pyrrole monomer is 1:10:10.
[0021] In a preferred embodiment of the present invention, in step B, the preparation conditions for PPyn are: reaction in an ice-water bath and in the dark for 24 hours.
[0022] In a preferred embodiment of the present invention, in step C, the PPyn, MWCNT and SNF are uniformly mixed in a mass ratio of 1:1:1 or 1:2:1 and then filtered to form a membrane.
[0023] The PPyn / MWCNT / SNF prepared by the method described in this invention has a morphology in which SNF serves as the basic framework, and the three one-dimensional nanomaterials PPyn, MWCNT and SNF interpenetrate and cross-link to form a connected porous network structure.
[0024] Another objective of this invention is to fabricate an all-solid-state wearable flexible supercapacitor. The positive and negative electrodes of this device are both PPyn / MWCNT / SNF, and the electrolyte is PVA / H2SO4 gel.
[0025] Application Experiment Steps:
[0026] Polyvinyl alcohol (PVA) powder was added to a 1 M H₂SO₄ solution; the preferred solid-liquid ratio of PVA to H₂SO₄ solution was 1 g : 10 mL. The mixture was then stirred continuously at 90–100 °C for 1 h until the PVA was completely dissolved, thus obtaining a PVA / H₂SO₄ gel electrolyte. After complete dissolution of PVA, the product was a uniform and transparent gel.
[0027] Two PPyn / MWCNT / SNF composite membranes, cut to the required size (e.g., 1 cm × 1 cm), are immersed in a PVA / H2SO4 gel electrolyte for 1–3 hours until fully wetted. After immersion, the membranes are removed and cured at room temperature. Then, the two electrodes are gently pressed together, and an appropriate amount of gel electrolyte is filled into the gaps to obtain an all-solid-state flexible supercapacitor.
[0028] The PPyn / MWCNT / SNF composite film prepared by this invention has the following advantages when used as an electrode material for flexible supercapacitors:
[0029] (1) Compared to existing electrochemical deposition methods, which suffer from the problem of active substances easily clogging substrate pores and performance degradation under long-term cycling, this invention employs a process of first synthesizing and then blending and filtering to interweave the three materials into a porous network. The polypyrrole utilizes a hollow nanotube structure, which can effectively buffer the volumetric strain during charge and discharge. This allows the electrolyte to continuously penetrate into the deep layers of the film during long-term cycling, achieving deep activation of the material. Tests show that the composite film of this invention exhibits an increase in capacitance retention after 5000 charge-discharge cycles, solving the problem of poor cycle life of traditional conductive polymer electrodes.
[0030] (2) This invention utilizes the morphology and properties of three materials: SNF provides mechanical support and high specific surface area, MWCNT forms long-range electron transport channels and double-layer capacitance, and hollow PPyn provides abundant pseudocapacitive active sites and shortens the ion diffusion path. The synergy of these three materials enables the composite film of this invention to exhibit high specific capacitance characteristics.
[0031] (3) The rigid polymer layer on the surface of traditional flexible substrates is prone to stress concentration during repeated bending, leading to cracking or peeling. This invention uses liquid-phase blending and filtration to embed polypyrrole nanotubes into a three-dimensional network with silk nanofibers as the framework and multi-walled carbon nanotubes as conductive bridges. The composite membrane retains a capacitance of up to 98.6% under large-angle bending of 0~150°, and a retention rate of 97.3% after 250 repeated bending at 90°, demonstrating resistance to fatigue shedding and meeting the application requirements of wearable electronic devices under complex deformation. Attached Figure Description
[0032] Figure 1 Scanning electron microscope (SEM) image of PPyn / MWCNT / SNF prepared in Example 1;
[0033] Figure 2 (a) Raman spectrum and (b) X-ray diffraction (XRD) pattern of PPyn / MWCNT / SNF prepared in Example 1;
[0034] Figure 3 The galvanostatic charge-discharge (GCD) curves of the PPyn / MWCNT / SNF prepared in Example 1 in a three-electrode system;
[0035] Figure 4 GCD curve of the flexible supercapacitor (two-electrode system) constructed from PPyn / MWCNT / SNF prepared in Example 1;
[0036] Figure 5 The flexible supercapacitor constructed from PPyn / MWCNT / SNF prepared in Example 1 is shown in (a) GCD curves under bending at 0-150° and (b) GCD curves after bending at 90° 250 times.
[0037] Figure 6 Capacitance retention of the PPyn / MWCNT / SNF prepared in Example 1 after 5000 cycles;
[0038] Figure 7 Capacitance retention of the flexible supercapacitor constructed from PPyn / MWCNT / SNF prepared in Example 1 after 5000 cycles. Detailed Implementation
[0039] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments to enable those skilled in the art to better understand the present invention, but the present invention is not limited to the following embodiments.
[0040] Example 1
[0041] A method for preparing a polypyrrole nanotube / multi-walled carbon nanotube / silk nanofiber composite membrane includes the following steps:
[0042] 14 g of choline chloride and 10.5 g of malonic acid were mixed and stirred at 80 °C for 2 h to obtain a transparent eutectic solvent. 0.2 g of degummed silk was added to this solvent, and the mixture was stirred in an oil bath at 100 °C for 40 h. The reaction was terminated by adding 10 mL of ethanol, and after centrifugation and washing, 0.16 g of SNF was obtained. The SNF was dispersed in 80 mL of deionized water to obtain a concentration of 2 mg / mL. -1 The dispersion.
[0043] 0.2 g of methyl orange was dissolved in 120 mL of deionized water, and 1.62 g of FeCl3·6H2O was slowly added under continuous stirring until the reaction was complete, forming a reddish-brown flocculent precipitate. 420 μL of pyrrole monomer was slowly added dropwise, and the reaction was carried out for 24 h in an ice-water bath and in the dark. The resulting PPyn was washed several times and dried in a vacuum oven at 60 °C for 24 h.
[0044] PPyn and MWCNT were added to 8 mL of SNF dispersion at a mass ratio of 1:1:1. The mixture was sonicated for 1 h and then stirred for 1 h to ensure uniform mixing of the three one-dimensional nanomaterials. The mixture was then vacuum filtered to form a film, which was subsequently freeze-dried at -60 °C for 24 h to obtain a PPyn / MWCNT / SNF film with a diameter of 20 mm.
[0045] The prepared PPyn / MWCNT / SNF composite film electrode operates at a current density of 5 mA cm⁻¹. -2 The discharge time was 259.0 s, corresponding to an areal capacitance of 1618.8 mF / cm². -2 (Three-electrode system, test area is 1 cm × 1 cm).
[0046] Figure 1 This is a SEM image of the PPyn / MWCNT / SNF prepared in this embodiment. Its morphology is based on SNF as the basic framework, and the three one-dimensional nanomaterials PPyn, MWCNT and SNF interpenetrate and cross-link with each other to form a three-dimensional interconnected network structure.
[0047] Figure 2 These are (a) Raman spectra and (b) XRD patterns of the PPyn / MWCNT / SNF prepared in this embodiment. Figure 2 (a) It can be seen that the Raman signal peaks of PPyn / MWCNT / SNF appear at 1345 and 1578 cm⁻¹. -1 At this location, the peak positions are close to those of PPyn and MWCNT; by Figure 2 (b) It can be seen that the diffraction peaks of PPyn / MWCNT / SNF are located at 2θ = 20.5°, 25.6° and 43.2°, which can be regarded as the superposition of the characteristic peaks of the three substances PPyn, MWCNT and SNF, indicating that the target product was successfully synthesized.
[0048] Figure 3 This is the GCD curve of the PPyn / MWCNT / SNF prepared in this embodiment in a three-electrode system. At a current density of 5 mA cm⁻¹ -2 At that time, the discharge time was 259.0 s, corresponding to an areal capacitance of 1618.8 mF / cm². -2 .
[0049] Figure 4 This is the GCD curve of the flexible supercapacitor (two-electrode system) constructed using PPyn / MWCNT / SNF prepared in this embodiment. At a current density of 5 mA cm⁻¹ -2 At that time, the discharge time was 156.2 s, corresponding to an areal capacitance of 976.3 mF / cm². -2 .
[0050] Figure 5 The figures show the GCD curves of (a) the flexible supercapacitor constructed from PPyn / MWCNT / SNF prepared in this embodiment during bending at 0-150° and (b) the GCD curve after bending at 90° 250 times. It can be seen that the device maintains good electrochemical stability under both deformation conditions, with capacitance retention rates of 98.6% and 97.3%, respectively.
[0051] Figure 6 This represents the capacitance retention of the PPyn / MWCNT / SNF prepared in this embodiment after 5000 cycles. As shown in the figure, the capacitance retention of this composite film electrode after 5000 charge-discharge cycles is 109.5%.
[0052] Figure 7 This represents the capacitance retention of the flexible supercapacitor constructed using PPyn / MWCNT / SNF prepared in this embodiment after 5000 cycles. As shown in the figure, the device retains 100.1% of its capacitance after 5000 charge-discharge cycles.
[0053] As can be seen from the above, PPyn / MWCNT / SNF becomes an ideal electrode material for flexible supercapacitors, exhibiting excellent electrochemical performance and mechanical flexibility. Test data from Example 1: In a three-electrode system, at a current density of 5 mA cm⁻¹... -2 The discharge time was 259.0 s, corresponding to an areal capacitance of 1618.8 mF / cm. -2 The capacitance retention rate after 5000 charge-discharge cycles is 109.5%; in a two-electrode system, at 5 mA cm⁻¹ -2 The discharge time was 156.2 s, corresponding to a specific capacitance of 976.3 mFcm. -2 The capacitance retention rate after 5000 charge-discharge cycles was 100.1%; the capacitance retention rates after 0-150° bending and 250 90° bending cycles were as high as 98.6% and 97.3%, respectively. Therefore, compared with the previously reported Pn-y@S / Mx (Journal of EnergyStorage 141 (2026) 119562), the PPyn / MWCNT / SNF composite film electrode has achieved significant improvements in both cycle stability and mechanical flexibility.
[0054] Example 2
[0055] A method for preparing a polypyrrole nanotube / multi-walled carbon nanotube / silk nanofiber composite membrane includes the following steps:
[0056] 14 g of choline chloride and 10.5 g of malonic acid were mixed and stirred at 80 °C for 2 h to obtain a transparent eutectic solvent. 0.2 g of degummed silk was added to this solvent, and the mixture was stirred in an oil bath at 100 °C for 40 h. The reaction was terminated by adding 10 mL of ethanol, and after centrifugation and washing, 0.16 g of SNF was obtained. The SNF was dispersed in 80 mL of deionized water to obtain a concentration of 2 mg / mL. -1 The dispersion.
[0057] 0.2 g of methyl orange was dissolved in 120 mL of deionized water, and 1.62 g of FeCl3·6H2O was slowly added under continuous stirring until the reaction was complete, forming a reddish-brown flocculent precipitate. 420 μL of pyrrole monomer was slowly added dropwise, and the reaction was carried out for 24 h in an ice-water bath and in the dark. The resulting PPyn was washed several times and dried in a vacuum oven at 60 °C for 24 h.
[0058] PPyn and MWCNT were added to 8 mL of SNF dispersion at a mass ratio of 1:2:1. The mixture was sonicated for 1 h, followed by stirring for 1 h to ensure uniform mixing of the three one-dimensional nanomaterials. The mixture was then vacuum filtered to form a film, which was subsequently freeze-dried to obtain a PPyn / MWCNT / SNF film with a diameter of 20 mm.
[0059] The prepared PPyn / MWCNT / SNF composite film electrode operates at a current density of 5 mA cm⁻¹. -2 The discharge time was 291.5 s, corresponding to an areal capacitance of 1821.9 mF / cm². -2 (Three-electrode system, test area 1 cm × 1 cm). Compared with the film of Example 1, the film of Example 2 has a slightly larger thickness and good mechanical flexibility.
[0060] Example 3
[0061] A method for preparing a polypyrrole nanotube / multi-walled carbon nanotube / silk nanofiber composite membrane includes the following steps:
[0062] 14 g of choline chloride and 10.5 g of malonic acid were mixed and stirred at 80 °C for 2 h to obtain a transparent eutectic solvent. 0.2 g of degummed silk was added to this solvent, and the mixture was stirred in an oil bath at 100 °C for 40 h. The reaction was terminated by adding 10 mL of ethanol, and after centrifugation and washing, 0.16 g of SNF was obtained. The SNF was dispersed in 80 mL of deionized water to obtain a concentration of 2 mg / mL. -1 The dispersion.
[0063] 0.2 g of methyl orange was dissolved in 120 mL of deionized water, and 1.62 g of FeCl3·6H2O was slowly added under continuous stirring until the reaction was complete, forming a reddish-brown flocculent precipitate. 420 μL of pyrrole monomer was slowly added dropwise, and the reaction was carried out for 24 h in an ice-water bath and in the dark. The resulting PPyn was washed several times and dried in a vacuum oven at 60 °C for 24 h.
[0064] PPyn and MWCNT were added to 8 mL of SNF dispersion at a mass ratio of 2:1:1. The mixture was sonicated for 1 h, followed by stirring for 1 h to ensure uniform mixing of the three one-dimensional nanomaterials. A PPyn / MWCNT / SNF film with a diameter of 20 mm was obtained by vacuum filtration and subsequent freeze-drying.
[0065] The prepared PPyn / MWCNT / SNF composite film electrode operates at a current density of 5 mA cm⁻¹. -2 The discharge time was 365.1 s, corresponding to an areal capacitance of 2281.9 mF / cm². -2(Three-electrode system, test area 1 cm × 1 cm). Compared with the membranes of Example 1 and Example 2, the membrane of Example 3 has weaker mechanical flexibility, and some active material will detach under repeated bending.
[0066] Comparative Example 1
[0067] A method for preparing a multi-walled carbon nanotube / silk nanofiber composite membrane includes the following steps:
[0068] 14 g of choline chloride and 10.5 g of malonic acid were mixed and stirred at 80 °C for 2 h to obtain a transparent eutectic solvent. 0.2 g of degummed silk was added to this solvent, and the mixture was stirred in an oil bath at 100 °C for 40 h. The reaction was terminated by adding 10 mL of ethanol, and after centrifugation and washing, 0.16 g of SNF was obtained. The SNF was dispersed in 80 mL of deionized water to obtain a concentration of 2 mg / mL. -1 The dispersion.
[0069] MWCNTs were added to 8 mL of SNF dispersion at a mass ratio of 1:1. The mixture was sonicated for 1 h and then stirred for 1 h. The mixture was then vacuum filtered to form a membrane, which was subsequently freeze-dried to obtain MWCNT / SNF with a diameter of 20 mm.
[0070] The prepared MWCNT / SNF was tested at a current density of 5 mA cm⁻¹. -2 The discharge time was 31.1 s, corresponding to an areal capacitance of 194.4 mF / cm². -2 (Three-electrode system, test area is 1 cm × 1 cm).
[0071] Comparative Example 2
[0072] A method for preparing a polypyrrole nanotube / silk nanofiber composite membrane includes the following steps:
[0073] 14 g of choline chloride and 10.5 g of malonic acid were mixed and stirred at 80 °C for 2 h to obtain a transparent eutectic solvent. 0.2 g of degummed silk was added to this solvent, and the mixture was stirred in an oil bath at 100 °C for 40 h. The reaction was terminated by adding 10 mL of ethanol, and after centrifugation and washing, 0.16 g of SNF was obtained. The SNF was dispersed in 80 mL of deionized water to obtain a concentration of 2 mg / mL. -1 The dispersion.
[0074] 0.2 g of methyl orange was dissolved in 120 mL of deionized water, and 1.62 g of FeCl3·6H2O was slowly added under continuous stirring until the reaction was complete, forming a reddish-brown flocculent precipitate. 420 μL of pyrrole monomer was slowly added dropwise, and the reaction was carried out for 24 h in an ice-water bath and in the dark. The resulting PPyn was washed several times and dried in a vacuum oven at 60 °C for 24 h.
[0075] PPyn was added to 8 mL of SNF dispersion at a mass ratio of 1:1. The mixture was sonicated for 1 h, followed by stirring for another 1 h. The mixture was then vacuum filtered to form a film, which was subsequently freeze-dried to obtain a PPyn / SNF film with a diameter of 20 mm.
[0076] The prepared PPyn / SNF was tested at a current density of 5 mA cm⁻¹. -2 The discharge time was 82.8 s, corresponding to an areal capacitance of 517.5 mF / cm². -2 (Three-electrode system, test area is 1 cm × 1 cm).
[0077] Comparative Example 3
[0078] A method for preparing a polypyrrole nanotube / multi-walled carbon nanotube composite film includes the following steps:
[0079] 0.2 g of methyl orange was dissolved in 120 mL of deionized water, and 1.62 g of FeCl3·6H2O was slowly added under continuous stirring until the reaction was complete, forming a reddish-brown flocculent precipitate. 420 μL of pyrrole monomer was slowly added dropwise, and the reaction was carried out for 24 h in an ice-water bath and in the dark. The resulting PPyn was washed several times and dried in a vacuum oven at 60 °C for 24 h.
[0080] 16 mg of MWCNT and 16 mg of PPyn were dispersed in 8 mL of deionized water at a mass ratio of 1:1, and the mixture was sonicated for 1 h, followed by stirring for 1 h. The dispersion was then vacuum filtered and freeze-dried to obtain PPyn / MWCNT with a diameter of 20 mm. The resulting PPyn / MWCNT film is brittle and easily broken, making it unsuitable for use as an electrode material in flexible supercapacitors.
[0081] Comparative Example 4
[0082] A method for preparing a polypyrrole nanotube / multi-walled carbon nanotube / silk nanofiber composite membrane includes the following steps:
[0083] 14 g of choline chloride and 10.5 g of malonic acid were mixed and stirred at 80 °C for 2 h to obtain a transparent eutectic solvent. 0.2 g of degummed silk was added to this solvent, and the mixture was stirred in an oil bath at 100 °C for 40 h. The reaction was terminated by adding 10 mL of ethanol, and after centrifugation and washing, 0.16 g of SNF was obtained. The SNF was dispersed in 80 mL of deionized water to obtain a concentration of 2 mg / mL. -1 The dispersion.
[0084] 0.2 g of methyl orange was dissolved in 120 mL of deionized water, and 1.62 g of FeCl3·6H2O was slowly added under continuous stirring until the reaction was complete, forming a reddish-brown flocculent precipitate. 420 μL of pyrrole monomer was slowly added dropwise, and the reaction was carried out for 24 h in an ice-water bath and in the dark. The resulting PPyn was washed several times and dried in a vacuum oven at 60 °C for 24 h.
[0085] PPyn and MWCNT were added to 8 mL of SNF dispersion at a mass ratio of 1:1:1. The mixture was sonicated for 1 h and then stirred for 1 h to ensure uniform mixing of the three one-dimensional nanomaterials. The mixture was then vacuum filtered to form a film, which was subsequently dried under vacuum at 60 °C for 24 h to obtain PPyn / MWCNT / SNF.
[0086] Compared to the membrane in Example 1, the prepared PPyn / MWCNT / SNF membrane wrinkled and its diameter decreased to 12 mm at a current density of 5 mA cm⁻¹. -2 The discharge time was 242.8 s, corresponding to an areal capacitance of 1517.5 mF / cm. -2 The capacitance retention rate after 5000 charge-discharge cycles was 102.5% (three-electrode system, test area 1 cm × 1 cm).
[0087] Comparative Example 5
[0088] A method for preparing a polypyrrole nanoparticle / multi-walled carbon nanotube / silk nanofiber composite membrane includes the following steps:
[0089] 14 g of choline chloride and 10.5 g of malonic acid were mixed and stirred at 80 °C for 2 h to obtain a transparent eutectic solvent. 0.2 g of degummed silk was added to this solvent, and the mixture was stirred in an oil bath at 100 °C for 40 h. The reaction was terminated by adding 10 mL of ethanol, and after centrifugation and washing, 0.16 g of SNF was obtained. The SNF was dispersed in 80 mL of deionized water to obtain a concentration of 2 mg / mL. -1 The dispersion.
[0090] MWCNTs were added to 8 mL of SNF dispersion at a mass ratio of 1:1. The mixture was sonicated for 1 h and then stirred for 1 h. The mixture was then vacuum filtered to form a membrane, which was subsequently freeze-dried to obtain MWCNT / SNF with a diameter of 20 mm.
[0091] MWCNT / SNF were soaked in 25 mL of pyrrole solution (1 M) for 2 h. Then, 25 mL of 0.5 M FeCl3 solution was added dropwise, and the mixture was reacted in an ice-water bath for 2 h. The product was washed alternately with deionized water and ethanol, and finally freeze-dried to obtain a polypyrrole nanoparticle / multi-walled carbon nanotube / silk nanofiber composite membrane.
[0092] The prepared polypyrrole nanoparticle / multi-walled carbon nanotube / silk nanofiber composite film was tested at a current density of 5 mAcm⁻¹. -2 The discharge time was 220.6 s, corresponding to an areal capacitance of 1378.8 mF / cm². -2 The capacitance retention rate after 5000 charge-discharge cycles was 75.2% (three-electrode system, test area 1 cm × 1 cm), which is significantly lower than that of the film in Example 1.
[0093] Comparative Example 6
[0094] A method for preparing a polypyrrole nanowire / multi-walled carbon nanotube / silk nanofiber composite membrane includes the following steps:
[0095] 14 g of choline chloride and 10.5 g of malonic acid were mixed and stirred at 80 °C for 2 h to obtain a transparent eutectic solvent. 0.2 g of degummed silk was added to this solvent, and the mixture was stirred in an oil bath at 100 °C for 40 h. The reaction was terminated by adding 10 mL of ethanol, and after centrifugation and washing, 0.16 g of SNF was obtained. The SNF was dispersed in 80 mL of deionized water to obtain a concentration of 2 mg / mL. -1 The dispersion.
[0096] MWCNTs were added to 8 mL of SNF dispersion at a mass ratio of 1:1. The mixture was sonicated for 1 h and then stirred for 1 h. The mixture was then vacuum filtered to form a membrane, which was subsequently freeze-dried to obtain MWCNT / SNF with a diameter of 20 mm.
[0097] MWCNT / SNF was immersed in 25 mL of electrolyte for 2 h. The electrolyte contained 0.2 M Na₂HPO₄, 0.002 M LiClO₄, and 0.15 M pyrrole. Using MWCNT / SNF as the working electrode, and a platinum sheet and a saturated calomel electrode as the counter and reference electrodes, deposition was performed at an anodic potential of 0.85 V for 3600 s. After the reaction, the product was repeatedly washed with deionized water, and finally freeze-dried to obtain a polypyrrole nanowire / multi-walled carbon nanotube / silk nanofiber composite membrane.
[0098] The prepared polypyrrole nanowire / multi-walled carbon nanotube / silk nanofiber composite film was tested at a current density of 5 mAcm⁻¹. -2 The discharge time was 233.1 s, corresponding to an areal capacitance of 1456.9 mF / cm. -2 The capacitance retention rate after 5000 charge-discharge cycles was 83.2% (three-electrode system, test area 1 cm × 1 cm), which is significantly lower than that of the film in Example 1.
[0099] The above description is an embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural or procedural transformations made using the present invention specification, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of the present invention.
Claims
1. A method for preparing a polypyrrole nanotube / multi-walled carbon nanotube / silk nanofiber composite membrane, characterized in that, Includes the following steps: (1) First, a eutectic solvent is prepared by choline chloride and malonic acid. Degummed silk is added to the eutectic solvent and heated and stirred. After the reaction is completed, silk nanofibers are obtained by separation and washing. The silk nanofibers are dispersed in water to obtain a silk nanofiber dispersion. (2) Methyl orange solution was mixed with ferric chloride to form a precipitate, and then pyrrole monomer was added and reacted under low temperature and light-proof conditions. After the reaction was completed, polypyrrole nanotubes were obtained by washing and drying. The molar ratio of methyl orange solution to ferric chloride is 1:8 to 1:12; the molar ratio of pyrrole monomer to ferric chloride is 1:0.8 to 1:1.
2. (3) Add polypyrrole nanotubes and multi-walled carbon nanotubes to the silk nanofiber dispersion, mix evenly, filter to form a film, freeze dry, and obtain a polypyrrole nanotube / multi-walled carbon nanotube / silk nanofiber composite film; the mass ratio of polypyrrole nanotubes, multi-walled carbon nanotubes and silk nanofibers is 1~2:1~2:
1.
2. The method for preparing the polypyrrole nanotube / multi-walled carbon nanotube / silk nanofiber composite membrane according to claim 1, characterized in that: In step (1), the eutectic solvent is prepared by mixing choline chloride and malonic acid in a molar ratio of 1:1 to 1:1.5 and stirring at 70 to 90 °C for 1 to 3 h. The mass ratio of the degummed silk to the eutectic solvent is 1:100 to 1:150; the heating and stirring reaction conditions are 90 to 110 °C for 36 to 48 h.
3. The method for preparing the polypyrrole nanotube / multi-walled carbon nanotube / silk nanofiber composite membrane according to claim 1, characterized in that: In step (2), the reaction conditions under low temperature and light protection are: reaction in an ice-water bath and in the dark for 12-36 h.
4. The method for preparing the polypyrrole nanotube / multi-walled carbon nanotube / silk nanofiber composite membrane according to claim 1, characterized in that: In step (3), the multi-walled carbon nanotubes (MWCNTs) have a purity ≥ 97 wt%, a length < 50 μm, and an outer diameter of 5~15 nm.
5. The method for preparing the polypyrrole nanotube / multi-walled carbon nanotube / silk nanofiber composite membrane according to claim 1, characterized in that: In step (3), the freeze-drying temperature is -60 ℃ and the time is 24 h.
6. A polypyrrole nanotube / multi-walled carbon nanotube / silk nanofiber composite membrane, characterized in that, Prepared by the preparation method according to any one of claims 1-5; The composite membrane has a three-dimensional porous network structure with silk nanofibers as the skeleton and polypyrrole nanotubes and multi-walled carbon nanotubes uniformly dispersed inside; and the polypyrrole nanotubes, multi-walled carbon nanotubes and silk nanofibers are interwoven.
7. A flexible supercapacitor, characterized in that, It includes a positive electrode, a negative electrode, and a gel electrolyte, wherein both the positive and negative electrodes are made of the polypyrrole nanotube / multi-walled carbon nanotube / silk nanofiber composite membrane as described in claim 6.
8. The flexible supercapacitor according to claim 7, characterized in that, The gel electrolyte is a PVA / H2SO4 gel electrolyte.